KERINDUAN PADA NARATIF Pola Retorika Komunikasi Politik Capres dan Cawapres THE YEARNING FOR NARATIVE The Pattern of Political Communication Rhetorics of President Candidates and Vice President Candidates - Prisgunanto, ilham (Universitas Prof. Dr. Moestopo (Beragama), 2009)
Have you been boring with pattern of rhetorics political Communications presidents candidate and vice presidents candidate in this election campaign? It . is true that political communications rhetorics presidens candidate and vice presidents candidate only majoring element of argumentatif not narrative. As a result that Election of Pilpres 20()9fully of falsehood, deception and betrayal to voter. Exactly voter fully hope patterns of narrative in political communications rhetorics with a which big swcy. Its proof of Voter swayed by buttonhole of Celebrities in legislative election then which assumed can make their better life. This condition show political life pattern Indonesia move to instan models.